Burnout in shadow teachers in teaching science to children with special needs: a case study at an inclusive elementary school in jambi - Hendra Budiono; Akmad Fikri Rosyadi; Silvina Noviyanti; Violita Zahyuni; Marites D Antonio (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The risk of burnout among shadow teachers significantly impacts the quality of services for children with special needs, so this issue needs to be considered, especially in inclusive education. The research purpose was to describe and examine aspects of burnout among shadow teachers in science education for children with special needs in inclusive elementary schools in Jambi. This study was qualitative and used a case study approach with three shadow teachers as subjects. The subjects were selected through purposive sampling and consisted of three shadow teachers with educational backgrounds and who had received training in handling children with special needs. Data collection techniques included observation and interviews. The results showed various forms of burnout in science teaching for children with special needs in inclusive schools, including emotional and physical exhaustion, depersonalization, and reduced self-esteem. Based on these results, it is necessary to develop a professional support system to prevent burnout and ensure the quality of assistance for children with special needs.